Liquid Assets and the Consumption Function - Cohen, Morris (The Review of Economics and Statistics, 1954)
THE role of liquid assets as well as other assets has received considerable attention in the war and postwar years, as economists and other interested observers have watched with obvious fascination the ever-mounting totals of currency, bank deposits, and particularly, government securities.2 These vast hoards of money and near money must have had, it was argued, an appreciable effect on consumers' decisions to spend and save, as well as on producers' decisions to invest. Some even felt that these assets were bound to result in a runaway inflation after the war and the wartime controls were over. Others minimized their influence. Still others looked upon liquid assets as an automatic stabilizer from a cyclical as well as a secular standpoint. Excluding the question of the effect of liquid assets on post World War II economic activity, liquid assets have also been used by various economic theorists for a wide range of hypotheses concerning consumer behavior, raising the asset effect almost to the level of a deus ex machina. Some have argued that liquid assets are a stabilizing secular influence,3 implicit in the classical position.4 Others have argued that liquid assets are the major factor accounting for the constancy of the ratio of saving to national product.5 Contrasted with the reliance of liquid assets as a secular force is the dominant role they assume for others in the cyclical process.' Finally, liquid assets have even been proposed as the major influence determining the shape of the cyclical consumption function.7 The position of the author is as follows: whatever the effect of liquid assets in a priori reasoning as we have just seen this is manifold it must be grounded in empirical observations.8 A. P. Lerner has expressed this in another and perhaps more interesting way by saying that liquidity is a commodity and should be looked upon as any other good or service in analyzing decisions to spend or save. Before turning to the evidence, such as it is, let us recall briefly the mechanics of the impact of liquid assets on consumption and investment.